Schematic language of public cultural spaces in traditional villages of Shaanxi Province and its suitable construction model - Jing Zhang; Yuchen Xia; Subin Xu; Bolin Lei (Journal of Asian Architecture and Building Engineering, 2025)
Public cultural spaces are essential for the development and cultural governance of Chinese villages. However, the wisdom behind constructing village public cultural spaces is often overlooked, limiting their adaptability to modern rural contexts. To stimulate the endogenous cultural power of villages, a comprehensive analysis of traditional village public cultural spaces is needed. This analysis should consider modern technological advancements and propose suitable building models. The study takes the public cultural spaces of 15 typical traditional villages in Shaanxi as examples, and utilizes the schematic language method to construct a village public cultural space vocabulary system that integrates “representation-connotation”. The results of the study show that the components of the public cultural space of traditional villages in Shaanxi are diversified. Its spatial characteristics and cultural connotations interact with each other, specifically in the four aspects of village development, natural resources, folk beliefs and clan culture. In addition, its suitability creation mode can be based on “syntax + structure” and “vocabulary + elements” to create wisdom features, realize inheritance design, help rural cultural governance and regional cultural heritage, and provide reference for rural space planning and design.